2013
DOI: 10.1371/journal.pone.0074429
|View full text |Cite
|
Sign up to set email alerts
|

Lungworm Infections in German Dairy Cattle Herds — Seroprevalence and GIS-Supported Risk Factor Analysis

Abstract: In November 2008, a total of 19,910 bulk tank milk (BTM) samples were obtained from dairy farms from all over Germany, corresponding to about 20% of all German dairy herds, and analysed for antibodies against the bovine lungworm Dictyocaulus viviparus by use of the recombinant MSP-ELISA. A total number of 3,397 (17.1%; n = 19,910) BTM samples tested seropositive. The prevalences in individual German federal states varied between 0.0% and 31.2% positive herds. A geospatial map was drawn to show the distribution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 27 publications
2
9
1
1
Order By: Relevance
“…Niedocenianym, często zapomnianym problemem w hodowli bydła jest inwazja nicieni płucnych, której występowanie u bydła wypasanego na pastwiskach potwierdzono u około 7% zwierząt. Również w innych krajach o podobnym klimacie stanowi ona lokalnie duży problem W Niemczech stwierdzana jest w badaniach serologicznych w około 17% prób i dotyka około 30% stad (27). Natomiast badania bezpośrednie (larwoskopowe), wykazujące inwazje w fazie patentnej, potwierdziły obecność tych nicieni u 0,9% badanych zwierząt (24).…”
Section: Ryc 3 Prewalencja Inwazji Pasożytów Wewnętrznych Bydła W Zunclassified
“…Niedocenianym, często zapomnianym problemem w hodowli bydła jest inwazja nicieni płucnych, której występowanie u bydła wypasanego na pastwiskach potwierdzono u około 7% zwierząt. Również w innych krajach o podobnym klimacie stanowi ona lokalnie duży problem W Niemczech stwierdzana jest w badaniach serologicznych w około 17% prób i dotyka około 30% stad (27). Natomiast badania bezpośrednie (larwoskopowe), wykazujące inwazje w fazie patentnej, potwierdziły obecność tych nicieni u 0,9% badanych zwierząt (24).…”
Section: Ryc 3 Prewalencja Inwazji Pasożytów Wewnętrznych Bydła W Zunclassified
“…Similarly, in the northern German region East Frisia, BTM ELISA showed 21.1% of dairy herds to be seropositive for D. viviparus on at least one sampling occasion in 2008 [ 12 ]. For the whole of Germany, Schunn et al [ 2 ] reported a BTM seroprevalence of 17.1%, with rates up to 31.2% in the federal state Saxony-Anhalt. In Ireland, a BTM seroprevalence of 62.8% was noted [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a significant detrimental effect on productivity of older cattle was observed (Charlier et al, 2009). Schunn et al (2013) reported seroprevalence rates up to 31.2% for German cattle herds for D. viviparus. Infections with the liver fluke Fasciola hepatica in adult cattle were mainly subclinical (Kaplan, 2001); nevertheless, substantial economic loss due to reduced milk production has been reported even for subclinical infections (Knubben-Schweizer et al, 2010).…”
Section: Introductionmentioning
confidence: 99%